EPCO-39. ADAPTIVE CONVERGENCE OF METHYLOMES REVEALS EPIGENETIC DRIVERS AND BOOSTERS OF REPEATED RELAPSES IN PATIENT-MATCHED CHILDHOOD EPENDYMOMAS AND IDENTIFIES TARGETS FOR ANTI-RECURRENCE THERAPIES. (14th November 2022) - Zhao, Sibo; Li, Jia Li; Zhang, Huiyuan; Qi, Lin; Du, Yuchen; Kogiso, Mari; Braun, Frank K; Teo, Wan-Yee; Lindsay, Holly; Baxter, Patricia A; Su, Jack M; Adesina, Adekunle; et al.
Abstract: Ependymoma (EPN) is the third most common brain tumor in children and frequently recurs. Here, we report an integrated longitudinal analysis of epigenetic, genetic and tumorigenic changes in 30 patient-matched repeated relapses obtained from 10 pediatric patients to understand the mechanism of recurrences. Genome-wide DNA methylation analysis revealed stable molecular subtypes and convergent epigenetic reprogramming during serial relapses of the 5 RELA and 5 PFA EPNs that paralleled with elevated patient-derived orthotopic xenograft (PDOX) (13/27) formation in the late relapses. Differentially methylated CpGs (DMCs) preexisted in the primary tumors and persisted in the relapses (driver DMCs) were detected, ranging from 51 hypo-methylated in RELA to 148 hyper-methylated DMCs in PFA tumors; while newly acquired DMCs sustained in all the relapses but was absent in the primary tumors (booster DMCs) ranged from 38- 323 hyper-methylated DMCs in RELA and PFA EPNs, respectively. Integrated analysis of these DMC associated DNA methylation regions (DMRs) and RNAseq in both patient and PDOX tumors identified a small fraction of the differentially expressed genes (4.6±4.4% in RELA and 4.5±1.1% in PFA) as regulated by driver DMRs (e.g., up-regulated CACNA1H, SLC12A7, RARA in RELA and HSPB8, GMPR, ITGB4 in PFA) and booster DMRs (including the sole upregulated PLEKHG1 in RELA and NOTCH, EPHA2, SUFU, FOXJ1 in PFA tumors). Most these genes were novel to EPN relapses. Seven DMCs in RELA and 22 in PFA tumors were also identified as potential relapse predictors. Finally, integrating DNA methylation with histone modification identified LSD1 as a relapse driver gene. Combined treatment of a novel inhibitor SYC-836 with radiation significantly prolonged survival times in two PDOX models of recurrent PFA. This high-resolution epigenetic and genetic roadmap of EPN relapse and our 13 new PDOX models should significantly facilitate biological and preclinical studies of pediatric EPN recurrences.